THE POLITICS OF REGIONALISM: ASSESSING THE IMPLEMENTATION OF ARTICLE 371J IN KARNATAKA - Udchanchi, Manohar; Khandimath, Meenakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article contributes to the broader discussion on regionalism and its political implications by analyzing the implementation of the Article 371Jof the Indian Constitution in Karnataka. This article was introduced in 2012 to provide special provisions to the Kalyana Karnataka region in order to correct historical inequities and promote regional development. This analysis examines both the efficacy of Article 371Jin fulfilling its purpose as well as the political maneuvers and contention it has invoked within its application. It examines the historical background of the region, its deprivation under the Nizams of Hyderabad, and the demand for special status thereafter. It discusses the salient features of Article 371Jincluding creation of separate development board, equitable distribution of funds, reservations in education and jobs, etc. This study examines the influence of Article 371Jon education, occupation, and economic & social development in the region through analysis of research papers, government reports, and news articles. However, although there have been many notable achievements in terms of infrastructure development and women's education and employment opportunities, progress is perceived to be limited, and a number of human development indicators show a slowing down of progress. This paper also discusses the political discourse and controversies with regard to the implementation of Article 371Jsuch as inconsistency in reservation schemes and eligibility criteria. The impact of federalism on regional inequalities: A comparative study of special provisions in other Indian states.